Development of Nutritional Biochemistry Learning Goals and Core Competencies in the Dental Hygiene Curriculum - Hye-Young Yoon; Sun-Jung Shin; Bo-Mi Shin; Hyo-Jin Lee; Jin-Sun Choi; Soo-Myoung Bae (치위생과학회지, 2022)
Background: In the dental hygiene curriculum, efforts are being made to introduce an integrated curriculum based on the competency of a dental hygienist. Because there is a connection and overlap in learning contents between Dental Nutrition and Oral Biochemistry, which are basic dental hygiene subjects, it is possible to integrate these two subjects. This study aims to derive Nutritional Biochemistry as an integrated curriculum for Dental Nutrition and Oral Biochemistry, and to develop learning goals and competencies for Dental Nutritional Biochemistry.Methods: The learning contents of the integrated curriculum were composed by referring to the contents of the Dental Nutrition and Oral Biochemistry textbooks, and learning goals were derived from the learning contents. Moreover, competency was developed by analyzing the duties of a dental hygienist that can be performed through the learning goals. The Delphi survey was conducted twice to verify the content validity ratio (CVR) of the competence and the learning goal of the integrated curriculum.Results: In the first Delphi survey, the CVR for two competencies was 0.56 or higher. Moreover, it was revised based on expert’s opinions, and as a result of the second Delphi survey after the revision, the CVR was either increased or maintained. Eighty-five learning goals were derived by referring to the textbook. According to CVR and expert opinions, after the first Delphi survey, the number of learning goals was reduced to 69. After the second Delphi survey, 68 learning goals were finally derived.Conclusion: The development process of the integrated curriculum conducted in this study can be utilized for integration between subjects in basic dental hygiene.